Boundary Objects, Social Meanings and the Success of New Technologies - Fox, Nick J. (Sociology (Oxford), 2011)
Boundary objects are entities that enhance the capacity of an idea, theory or practice to translate across culturally defined boundaries, for example, between communities of knowledge or practice. This concept thus has potential to both explain and predict technology adoption; however, it remains sociologically under-theorized. This article assesses, by recourse to a historical case study of innovations in surgical sterility, how boundary objects work and their relationship to social meanings within communities of practice. It is concluded that not only are there positive and negative boundary objects, but that technological devices or processes may themselves act as facilitative or inhibitory boundary objects during innovation. The approach set out here has potential as a sociologically informed model of improving adoption of technologies and policies by managing the positive and negative social meanings of technology objects.